Perancangan Sistem Informasi Akuntansi Kas Berbasis Desktop Di Poliklinik Pusdikmin Lemdiklat Polri - Nursaila Nursaila Nursaila (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
This study aims to create an accounting information system that can be used at the Poliklinik Pusdikmin Lemdiklat Polri. The data collection technique used by the author is using descriptive analysis by means of interviews, observations and also the study of the available data literature. And the software development method used is the waterfall method. Even though the recording and reporting of capitation funds is semi-computerized using Microsoft Excel and Microsoft Word...but there is still a high possibility of errors in data collection, and can allow data loss, as well as delays. Therefore, the Pusdikmin Polyclinic of the National Police Lemdiklat needs a system that can help simplify the reporting process. So the author gives advice by designing a cash accounting information system by modeling structured analysis including flowmaps, context diagrams, Entity relationship diagrams (ERD), desktop-based data flow diagrams (DFD) using Microsoft studio 2017 and MySQL. By testing the system using the Blackbox testing method. The author hopes that this application can facilitate the work process and speed up the effectiveness of cash recording and report generation.